Measuring the economic benefits of protecting the Parque Natural do Sudoeste Alentejano e Costa Vicentina from commercial tourism development : results from a contingent valuation survey - Nunes, Paulo A.L.D. (2018)
This paper focus on a contingent valuation application as to measure the value that the Portuguese households are willing to pay for the recreation and biodiversity benefits provided by a Natural Park in Portugal. A national survey was designed and implemented. It gathered 1678 respondents and focus on three tourism development policy options for the Park. We refer to (1) the Wilderness- Area commercial tourism development scenario; (2) the Recreational-Area commercial tourism development scenario and, finally, a scenario version which is characterized by the tourism development of both Wilderness and Recreational Areas of the Natural Park. The results show that the Portuguese evaluate the Wilderness-Area and the Recreational-Area differently. In particular, the Portuguese show a higher willingness to pay for preserving the Wilderness-Area free from any commercial tourism development. However, we find no statistical difference between the willingness to pay for the Wilderness-Area and the willingness to pay for the Wilderness-Area jointly with the Recreational-Area. The last result can be interpreted as a consequence of the lack of credibility of the protection scenarios or, more interestingly, as pointing to the eventual presence of warm glow in the stated willingness to pay responses.